Didaktika: Med dediščino preteklosti in sodobnim utripom učenja in poučevanja - Javornik, Marija; Ivanuš Grmek, Milena; Mithans, Monika (2025)
Didactics: Between the Heritage of the Past and the Modern Pulse of Learning and Teaching, Book of Abstracts. The conference book of abstracts presents a diverse and timely collection of contributions in the field of education and pedagogy. The central section features topics such as teacher reflection, process-oriented learning, and the contemporary challenges of higher education didactics. Discussions also address teacher stress and burnout, as well as student participation in academic decision-making. In the section on subject didactics, authors explore the significance of cultural heritage, mathematical concepts, history teaching, and practical aspects of biology instruction. Contributions on language teaching emphasize the importance of critical reading, language policy, and teaching methodology. The teaching section highlights modern didactic approaches, outdoor education, and theoretical models. The final section includes papers on counseling, the role of art in education, and the challenges of adult education. Overall, the book reflects a rich interplay between theoretical insights and practical solutions aimed at enhancing the quality of the educational process.
Keywords: teacher reflection; higher education didactics; process-oriented learning; student participation; subject didactics; teaching; counseling; cultural heritage; language instruction; didactic methods; adult education; quality of education